Rigid-flexible Coupling Dynamics and Fatigue Life Evaluation of Wheel Reducers Based on the Load Spectrum - Yang Siyuan; Wan Yipin; Zhang Lei; Song Xuding (Jixie chuandong)
Aiming at the fatigue problem of the wheel edge reducer gear system of the drive axle of the loader, the dynamics simulation and fatigue life evaluation are carried out. Firstly, based on rigid-body dynamics and rigid-flexible coupling dynamics, the variation of the contact force between the solar wheel and the planetary wheel is analyzed, and compared with the theoretical calculation value of the contact force, the credibility of the model is verified. Then, the sun wheel is considered as a flexible body, and the stress-time history of the tooth root fatigue risk point is extracted. The peak-valley extraction and wavelet removal are carried out for the stress-time history. The influence of average stress is corrected by Goodman formula, and a one-dimensional stress spectrum is prepared. Finally, the crack initiation life of the tooth root is calculated and evaluated according to the linear fatigue damage accumulation criterion and compared with the experimental results. The results show that the crack initiation life of the solar wheel based on the rigid-flexible coupling dynamic model is 42 709 h, and the relative errors of the two experimental results are 1.5% and 3.7% respectively. The rationality of the evaluation method is verified, which provides a reference for the optimization and anti-fatigue design of the gear system.